THU0166 HOW EFFECTIVE AND SAFE ARE BIOLOGIC DISEASE-MODIFYING ANTIRHEUMATIC DRUGS IN ELDERLY AND VERY ELDERLY PATIENTS WITH RHEUMATOID ARTHRITIS?. (2nd June 2020) - Freitas, R.; Madeira, N.; Fernandes, B. M.; Costa, F.; Santiago, M.; Neto, A.; Azevedo, S.; Madruga Dias, J.; Couto, M.; Bernardes, M.; Cunha Miranda, L.; Polido-Pereira, J.; et al.
Abstract : Background: The proportion of elderly patients is increasing in the rheumatoid arthritis (RA) population. However, data on drug effectiveness and safety in these patients is scarce. Objectives: To assess effectiveness and safety of biologic Disease-Modifying Antirheumatic Drugs (bDMARD) in elderly and very elderly RA patients. Methods: Prospective cohort-study of RA patients registered at Reuma.pt starting a 1st bDMARD. Treatment persistence, EULAR response at 6 and 12 months, and adverse events (AE) were compared between adults (<65 years-old), elderly (65-74 years-old) and very elderly (≥ 75years-old). Results: 2401 patients were included, of which 379 were elderly and 83 very elderly. Elderly and very elderly had higher disease activity at baseline and more comorbidities. Elderly patients started bDMARD later in the course of RA (table 1 ). Crude and adjusted bDMARD treatment persistence was similar in the 3 groups (p=0.07, Graph). At 6/12 months, EULAR response was achieved by 81.6%/83.3%, 75.2%/68.5% and 82.6%/84.2% of adults, elderly and very elderly, respectively (table 2 ). Except for a lower response rate at 12 months in the elderly group, the EULAR response was comparable in the 3 groups. The same results were observed after adjustment for baseline characteristics, namely the chance of achieving EULAR response was not different in adults and very elderly (OR 0.78, 95% CI 0.19 to 3.2). Also, the variation of DAS, CDAI and SDAI at 6 months and 12 months were comparable in the 3 groups. AE were reported in 21%/22.5%/22.9% of adult/elderly/very elderly patients, respectively. The rate of AE per 100 patient-years was lower in adults when compared to elderly and very elderly (6.4, 13.5 and 14.7, respectively) (table 2 ). Also the rate of severe AE (SAE) was higher in very elderly (4.29 per 100 patient-years) when comparing to adults and elderly (1.03 and 1.94 respectively). Conclusion: The persistence on 1st bDMARD was similar in adults, elderly and very elderly RA patients. Though older patients have more comorbidities and more active disease at baseline, treatment with biologics was effective and with an acceptable safety profile. However, it is important to take into account the higher risk of AE and SAE in older patients. In conclusion, this study supports the use of bDMARD treatment in elderly and very elderly RA patients. Graph – Persistence in bDMARD Disclosure of Interests: Raquel Freitas: None declared, Nathalie Madeira: None declared, Bruno Miguel Fernandes: None declared, Flavio Costa: None declared, Mariana Santiago: None declared, Agna Neto: None declared, Soraia Azevedo: None declared, João Madruga Dias: None declared, Maura Couto: None declared, Miguel Bernardes Speakers bureau: Abbvie, Amgen, Biogen, Eli-Lilly, Glaxo-Smith-Kline, Pfizer, Janssen, Novartis, Luís Cunha Miranda: None declared, Joaquim Polido-Pereira: None declared, Joao Eurico Fonseca: None declared, Maria Jose Santos Speakers bureau: Novartis and Pfizer